Aragonite toothpaste for management of dental calculus: A double‐blinded randomized controlled clinical trial. Issue 4 (14th April 2022) - Al‐Hashedi, Ashwaq A.; Dubreuil, Nadia; Schwinghamer, Timothy; Dorzhiyeva, Subad; Anweigi, Lamyia; Emami, Elham; Tamimi, Faleh
Abstract: Objectives: Aragonite from animal origin such as cuttlefish bone powder is an abrasive with hardness properties ideal for calculus removal. The purpose of this randomized controlled trial was to test the efficacy of a cuttlebone‐derived aragonite toothpaste in removing dental calculus. Materials and Methods: Eighty‐one patients who fulfilled the inclusion criteria were blindly and randomly assigned into two study groups. The intervention treatment group ( n  = 40) received cuttlebone toothpaste (Dr. D‐Tart) and the control group ( n  = 41) received an off‐the‐shelf commercial toothpaste (Crest). Evaluations were performed before and after scaling and polishing procedures done at 3 months in order to evaluate the toothpaste's ability to remove calculus and to prevent calculus formation. Calculus, stains, plaque, and gingival indices scores, and patient satisfaction surveys were compared at baseline (first visit), 3, and 9 months, using generalized linear models and Wald's χ 2 test. Results: At the end of the 3‐month period, the intervention group showed a 30% reduction in total calculus compared to the baseline score ( p  = .0006) and 45% less total calculus compared to the control group ( p  = .0001). Six months after scaling, the mean calculus score for Crest users was 42% higher than that for Dr. D‐Tart users ( p  = .0692). There was a significant improvement in the gingival health of cuttlebone toothpaste users at the observed intervals, and both kinds of toothpaste achieved comparable results in terms of plaque and stains removal. Conclusions: Aragonite toothpaste can remove calculus, prevent calculus formation, and improve gingival health. Patients are generally satisfied with the performance of the aragonite toothpaste. Clinical significance: Animal‐derived aragonite toothpaste (Dr. D‐Tart) shows promising efficacy in removing calculus, preventing calculus formation, and for the improvement of gingival health. Clinical trial ID: A08‐M35‐16B.